Unveiling the credence value: Consumer premium for pesticide-free practices in organic winegrowing - Noah Larvoe; Zein Kallas (Future Foods)
The global rise in organic wine production and consumption reflects a growing consumer preference for environmentally sustainable options and a greater willingness to pay (WTP) compared to conventional alternatives. Despite this trend, few studies have isolated the specific influence of reduced synthetic pesticide use—a key criterion of organic certification—on consumer WTP. Existing research often treats organic production as a monolithic attribute, overlooking how consumers value specific practices, particularly in processed products such as wine. This study addresses this gap by estimating the contribution of pesticide-free practices to the overall WTP for organic wine and examining how this valuation varies based on knowledge, attitudes, and demographics. A reference price-dependent discrete choice experiment was conducted with 1,070 organic wine consumers across five Euro-Mediterranean wine-producing countries: France, Greece, Italy, Portugal, and Spain. The results show that up to 74% of the organic wine price could be attributed to pesticide-free practices, with notable heterogeneity across the five countries. Three distinct consumer segments emerged: awareness-driven, certification-trusting, and price-sensitive. These findings underscore the strong consumer preference for pesticide-free production and suggest that credible certification schemes and targeted marketing strategies could encourage pesticide reduction, even in conventional vineyards. Such efforts could support the sustainability goals outlined in the EU Green Deal and provide economic incentives for conventional winegrowers to transition toward more environmentally friendly practices.